Waggle Dances and Azimuthal Windows - O. Duangphakdee; S. E. Radloff; C. W. W. Pirk; H. R. Hepburn (Psyche: A Journal of Entomology)
Because the waggle dances of honeybees contain celestial components, modifications of the dances occur with changing celestial moves relative to a honeybee nest. Since the direction of a particular resource is static, the dances must alter to compensate for the sun's passage. The position of the sun is seasonal between the Tropics of Cancer and Capricorn so that turns at the end of waggle runs will vary with season and latitude. The bees are confronted with a new difficulty when the sun closely approaches its zenith because only slight errors in the bees' estimation of the relative positions of the sun and zenith generate very large errors. So, the sun compass loses its usefulness when at its zenith. We review experiments and observations on both foraging and absconding in relation to the azimuth. The honeybees' solution for the paradox of the azimuth includes an azimuthal lull, preferences, and time windows.